ANALISIS PERUBAHAN PENUTUPAN KAWASAN HUTAN MANGROVE DI KECAMATAN PERCUT SEI TUAN TAHUN 2011 DAN 2014 - Rohana Megawati Sirait; Anita Zaitunah; Budi Utomo (Program studi Kehutanan USU, 2015)
This study aims to know and calculate the mangrove forest cover change in the District Percut Sei Tuan from 2011 up to 2014. This study was located in mangrove forests area District Percut Sei Tuan by using satellite images of Landsat 7 and 8. The research method used was a supervised classification. Analysis of the data for image interpretation by using monogram North Sumatera. The results showed that land cover changes from 2011 to 2014 including farms, oil palm plantations, rice fields, vacant land/open land, secondary mangrove, shrub swamp, and settlements. Changes in the extent of mangrove forest was 638,83 ha in 2014.Keywords: land coverage, mangrove forest area, Landsat imagery